2014
DOI: 10.1371/journal.pone.0096522
|View full text |Cite
|
Sign up to set email alerts
|

CaMKII Binding to GluN2B Is Differentially Affected by Macromolecular Crowding Reagents

Abstract: Binding of the Ca2+/calmodulin(CaM)-dependent protein kinase II (CaMKII) to the NMDA-type glutamate receptor (NMDAR) subunit GluN2B controls long-term potentiation (LTP), a form of synaptic plasticity thought to underlie learning and memory. Regulation of this interaction is well-studied biochemically, but not under conditions that mimic the macromolecular crowding found within cells. Notably, previous molecular crowding experiments with lysozyme indicated an effect on the CaMKII holoenzyme conformation. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…A caveat to this previous study, however, is that lysozyme has been shown to bind directly to Ca 2+ /CaM30, and, therefore, potentially complicates the interpretation of these results, especially regarding effects on the apparent EC 50 . Thus, we first compared the effects of molecular crowding by 150 mg ml −1 lysozyme and the putatively more inert molecule bovine serum albumin (BSA) (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…A caveat to this previous study, however, is that lysozyme has been shown to bind directly to Ca 2+ /CaM30, and, therefore, potentially complicates the interpretation of these results, especially regarding effects on the apparent EC 50 . Thus, we first compared the effects of molecular crowding by 150 mg ml −1 lysozyme and the putatively more inert molecule bovine serum albumin (BSA) (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…; Goodell et al . ). The quantified amount of CaMKII in the pellet was normalized, with the aggregation in presence of ADP (≥ 100 μM) without inhibitors in the same experiment set to 100.…”
Section: Methodsmentioning
confidence: 97%
“…Cell culture, transfections, protein preparations, and Western analysis were done as previously described (Barcomb et al, 2013; 2014; 2015; Bayer et al, 2001; 2006; Coultrap and Bayer, 2012b; 2014; Goodell et al, 2016; 2014; O'Leary et al, 2011; Singla et al, 2001; Vest et al, 2007) and are detailed in the Supplemental Experimental Procedures. Antibodies and dilutions are shown in Supplemental Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…In vitro protein binding experiments were done as previously described (Goodell et al, 2014) using immobilized GST-GluN2Bc on sepharose or magnetic beads. DAPK1 constructs (varying concentrations or 1 µM for comparison between constructs) were bound in either EGTA or varying Ca 2+ /CaM as indicated.…”
Section: Methodsmentioning
confidence: 99%